Penghampiran Linear dan Kuadratik untuk Kaedah Kamiran Sempadan bagi Persamaan Laplace Tiga Dimensi dengan Putaran Simetri. - Taib, Bachok (Universiti Putra Malaysia Press, 1993)
The boundary integral method is used for solving the three dimensional Laplace's equation with rotational symmetry numerically. Linear and quadratic approximations are presented. Accuracy for both linear and quadratic approximation will be compared.